A new methodology for end-of-life product disassembly analysis - Feri Afrinaldi, 1982-, author; Muhamad Zameri Mat Saman, author; Awalluddin Mohamad Shaharoun, author (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL